Electrochemically modulating the geometry of gold nanostructures for enhanced electrochemistry and antifouling performance - Chen, Feixiong; Mostafiz, Bahar; Peltola, Emilia (Elsevier BV, 2026)
Background: Biofouling, caused by nonspecific adsorption of biomolecules, compromises electrochemical sensor performance by blocking surface access and reducing sensitivity and reproducibility. Surface nanostructuring offers an effective route to counteract this effect and improve sensor reliability in complex biological media. However, their contributions to antifouling performance, caused by increases in electroactive surface area or the complexity of structured morphologies, have not been systematically investigated.
Results: We report a tuneable electrodeposition-based strategy to engineer gold nanostructures (GNS) with distinct geometries. Constant potential deposition (CPD) produced coral-shaped GNS, while pulsed-wave deposition (PWD) generated pine-needle-shaped GNS through a distinct anisotropic growth mode. Morphologies were confirmed by SEM, XPS, XRD, and water contact angle analysis. Electrochemical characterization (CV, SWV, EIS) revealed enhanced redox behaviour and reduced impedance in all GNS-modified electrodes compared to the unmodified gold-based screen-printed electrode (SPE). Pine-needle GNS demonstrated superior antifouling performance, retaining 59 % redox signal in bovine serum albumin, compared to 43 % for coral-shaped GNS. Crucially, by using a stepwise surface engineering approach with minimal variation in material composition, we demonstrated that nanostructure geometry, not just surface area, is the dominant factor governing both antifouling behaviour and electrochemical performance. A unifying relationship between electroactive surface area (ESA) and redox response was also observed across all GNS types.
Significance: This study highlights nanostructure shape as a key design parameter for enhancing sensor performance in biological environments. The modular deposition approach provides a robust platform for fabricating antifouling, high-sensitivity electrodes. These findings support future development of electrochemical sensors for clinical diagnostics and point-of-care applications.